1982
DOI: 10.1002/ajh.2830120406
|View full text |Cite
|
Sign up to set email alerts
|

Indications for platelet transfusion in children with acute leukemia

Abstract: In an attempt ot determine the indications for platelet transfusion in thrombocytopenic patients, we randomized 56 children with acute leukemia to one of two regimens of platelet transfusion. The prophylactic group received platelets when the platelet count fell below 20,000 per mm3 irrespective of clinical events. The therapeutic group was transfused only when significant bleeding occurred and not for thrombocytopenia alone. The time to first bleeding episode was significantly longer and the number of bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
125
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 6 publications
0
125
0
Order By: Relevance
“…Thus, a therapeutic platelet transfusion policy is a promising approach, but its actual efficacy was unproven because of the small numbers of patients included in these prior studies. [16][17][18] There is a long-standing controversy in the scientific community of hematologists and oncologists as to whether standard prophylactic platelet transfusions are necessary or whether this strategy should better be replaced by a therapeutic transfusion strategy. 10,17,[19][20][21][22] During the last 20 years, the recommendations of the American Society of Clinical Oncology reduced the trigger for prophylactic platelet transfusion from 20 Â 10 9 /l down to 10 Â 10 9 /l for thrombocytopenia following intensive chemotherapy or after hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a therapeutic platelet transfusion policy is a promising approach, but its actual efficacy was unproven because of the small numbers of patients included in these prior studies. [16][17][18] There is a long-standing controversy in the scientific community of hematologists and oncologists as to whether standard prophylactic platelet transfusions are necessary or whether this strategy should better be replaced by a therapeutic transfusion strategy. 10,17,[19][20][21][22] During the last 20 years, the recommendations of the American Society of Clinical Oncology reduced the trigger for prophylactic platelet transfusion from 20 Â 10 9 /l down to 10 Â 10 9 /l for thrombocytopenia following intensive chemotherapy or after hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that prophylactic platelet transfusions reduce the incidence of bleeding, 3 the optimal dose of platelets to transfuse is controversial. 5 Roy et al randomly assigned 62 patients to receive 1 of 2 doses, based on units per body weight, when the platelet count was Յ 25 000/L.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the 1970s, Murphy et al found that children with leukemia experienced an average of 7.9 significant bleeds (nasal/oral bleeding requiring packing, gross gastrointestinal or genitourinary bleeding, CNS bleeding, or bleeding that required red cell transfusion) per 100 months of observation without prophylactic platelet transfusions versus 1.9 for children given prophylactic platelet transfusions. 3 However, relevance of these data is still questionable for the reasons discussed earlier, and a prophylactic platelet transfusion trigger of 20 000 platelets/L was used versus the 10 000 platelets/L trigger that is currently recommended. 4 Furthermore, the source of platelet concentrates (apheresis vs whole blood-derived) and the quality and quantity of platelets transfused were probably quite different and perhaps inferior, compared with current practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients in the prophylactic arm suffered from more prolonged hemorrhagic episod possibly as a result of the development of HLA alloimmunization and refractoriness to randomdonor platelet support. Other data supporting a prophylactic policy were published by Gaydos et al 43 and by Slichter and Harker. 44 In a study dating from the early 1960s, Gaydos et al showed that hemorrhage was more frequent and severe at platelet counts below 5,000/µL, whereas it occurred in 8% and 4% of hospital days at counts exceeding 10,000/µL and 20,000/µL, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…44 In a study dating from the early 1960s, Gaydos et al showed that hemorrhage was more frequent and severe at platelet counts below 5,000/µL, whereas it occurred in 8% and 4% of hospital days at counts exceeding 10,000/µL and 20,000/µL, respectively. Other data supporting a prophylactic policy were published by Gaydos et al 43 and by Slichter and Harker. 44 In a study dating from the early 1960s, Gaydos et al showed that hemorrhage was more frequent and severe at platelet counts below 5,000/µL, whereas it occurred in 8% and 4% of hospital days at counts exceeding 10,000/µL and 20,000/µL, respectively.…”
Section: Discussionmentioning
confidence: 92%